Assessing regional production potential to strengthen the security of supply in strategic products - Matthias Firgo; Fabian Gabelberger; Andreas Reinstaller; Yvonne Wolfmayr (Austrian Institute of Economic Research (WIFO), 2024)
Recent shocks to global value chains and geopolitical tensions have reignited the debate on domestic production of strategic goods and technologies. This paper proposes an analytical framework for identifying and prioritising activities and regions for potential reshoring policies combining methods from international, industrial and regional economics. Particularly, we assess import dependencies, potentials and risks for competitive domestic production, and evaluate the embeddedness of existing and potential production in cognitively and technologically related activities in a region. We highlight the relevance of this approach as a policy tool using industries manufacturing strategic products and regions in Austria as an example.
Keywords: F14; F60; L52; L60; R12; R58; 330; Strategic products; reshoring; industrial policy; comparative advantage; import dependency; skill-relatedness